Latinx college students : innovations in mental health, advocacy, and social justice programs - Maldonado, José M.; Johnson, Adrianne Lynn (Identity & practice in higher education-student affairs., 2024)
"Counselors and educators are advocates for understanding ourselves, multiculturalism, and diversity in a societal climate of division. Provided the recent political coup and exclusion ideology, Latino Male students are marginalized because of cultural identity (Machismo) and cultural values. Due to the controversial nature of Machismo, masculinity, and language with Latino Males, multicultural educators are constantly silenced in universities by political correctness and censorship. Specifically, Latino Males are a direct target for incidences of racism, microaggressions, and oppression in our society. Colleges, universities, and counseling field has been moving forward slowly in its scope of "inclusion advocacy" for Latino Male students. There is a dearth in the empirical research on Latino Male experiences of otherness, indifference, and exclusion. The proposed textbook will establish viable, strategies to deepen cultural competence and inclusion advocacy. A competent framework for engagement is desperately needed in areas of inclusion, advocacy, and social justice for Latino Males. The convergence of sociopolitical views on diverse relationships has ignited an era of unrest, exclusion ideology, and remnants of mental distress and trauma in Latino communities. The textbook/reader will specifically address the issues of Latino Male Machismo in colleges and universities. The authors will produce a variety of important readings (chapters) about Latino Male students, Otherness, and strategies for cultural inclusion of identity, values, and practices. The potential contributions from this research will provide a foundation for implementing innovative, inclusion programs for Latinx students as well. To further add content, critical incidences of bias, discrimination, otherness, and exclusion will be addressed in a manner that promotes a new form of connectedness for Latino Males in colleges and universities. The intended audience for this textbook/reader are counselor educators, student affairs professionals, counselors, and university counselors"--